2016
DOI: 10.5424/fs/2016251-07955
|View full text |Cite
|
Sign up to set email alerts
|

The effects of fire severity on ectomycorrhizal colonization and morphometric features in Pinus pinaster Ait. seedlings

Abstract: Aim of the study: Mycorrhizal fungi in Mediterranean forests play a key role in the complex process of recovery after wildfires. A broader understanding of an important pyrophytic species as Pinus pinaster and its fungal symbionts is thus necessary for forest restoration purposes. This study aims to assess the effects of ectomycorrhizal symbiosis on maritime pine seedlings and how fire severity affects fungal colonization ability.Area of study: Central Spain, in a Mediterranean region typically affected by wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…According to Teketay (2001), deforestation is immense and estimated between 150000 -200000 ha of land per year. Factors contributing to habitat degradation, such as fires, are also affecting the fungal communities in forest systems (Vásquez-Gassibe et al, 2016), which is also a recurrent phenomenon in the natural forest systems in the country. This adversely influences the macrofungi and diminishes their diversity and production (Miller & Lodge, 1997).…”
Section: Threats and The Need For Conservationmentioning
confidence: 99%
“…According to Teketay (2001), deforestation is immense and estimated between 150000 -200000 ha of land per year. Factors contributing to habitat degradation, such as fires, are also affecting the fungal communities in forest systems (Vásquez-Gassibe et al, 2016), which is also a recurrent phenomenon in the natural forest systems in the country. This adversely influences the macrofungi and diminishes their diversity and production (Miller & Lodge, 1997).…”
Section: Threats and The Need For Conservationmentioning
confidence: 99%
“…In an experiment that used simulated (furnaceincinerated) burned soil, S. bovinus enhanced shoot biomass of P. pinaster seedlings; however nonmycorrhizal seedlings were larger in unburned soil where nutrient availability could have been higher (Sousa et al 2011). In a second study, Pinus pinaster seedlings planted in blocks of burned soil in the greenhouse were larger than controls in unburned soil, but this could not be attributed to mycorrhization since this was confounded with soil properties; they suggested that a control of sterilized burn soil should have been added (Vásquez-Gassibe et al 2016). In the field, growth and survival appear to increase when seedlings are both inoculated with Suillus and planted on burns (Lonergan et al 2014;Asebrook and Hintz 2015).…”
Section: Effect Of Suillus Species On Seedlings In Burn Soilmentioning
confidence: 98%
“…Greenhouse bioassays have been used to successfully detect viable ectomycorrhizal fungi in burn or simulated burn soil (Baar et al 1999;Kjøller and Bruns 2003;Izzo et al 2006;Peay et al 2009;Buscardo et al 2010;Kipfer et al 2010;Sousa et al 2011;Glassman et al 2016;Vásquez-Gassibe et al 2016). When uncolonized P. albicaulis seedlings were planted in unsterilized burn soil in the present greenhouse bioassay, no ectomycorrhizal fungi were detected.…”
Section: Ectomycorrhizal Fungi In Burn Soilmentioning
confidence: 99%
See 2 more Smart Citations